Business Model Canvas as a Strategic Planning Tool in Early Childhood Education Institutions - Zebua, Syukurman; Sulistyowati, Retno Wuri; Harmawati, Diah (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to analyze the application of the Business Model Canvas (BMC) as a strategic planning tool in a non-profit, community-based Early Childhood Education institution, using a case study of ECE Kemah Pujian in East Jakarta. The research contributes to the understanding of how BMC can be adapted within rural education settings characterized by diverse socio-cultural dynamics. Employing a descriptive qualitative approach, data were collected through in-depth interviews with school administrators, parents, and community partners, as well as through field observations and institutional documentation. The findings reveal that ECE Kemah Pujian has successfully developed a business model that emphasizes active community participation, the integration of local values, and flexible financing strategies. The institution’s main value proposition lies in providing early childhood education that is safe, affordable, and contextually relevant to local social needs. Its funding, sourced from voluntary contributions, village funds, and community donations, illustrates a high level of community empowerment. The interconnection of all nine BMC components, such as partnerships with local government and community leaders (key partnerships), and personalized approaches to engaging with parents (customer relationships), plays a crucial role in sustaining the institution. This study confirms that BMC can be effectively applied in non-profit educational settings and may serve as a strategic model for similar institutions in other areas. Furthermore, it demonstrates how local value-based business modeling can enhance the role of education institutions as integral actors in grassroots social development.